L’évaluation des politiques en relations internationales : Le cas de la coopération franco-québécois en éducation - Donneur, André; Brassard, Lise; Gravel, Pierre; Delay, Daniel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
Taking into account recent policy analysis and evaluation theories which have been rarely applied international relations up till now, we attempted to construct a framework which we used to evaluate France-Quebec policies of cooperation in the field of education. Having identified the objectives of this cooperation, we verified wether these objectives were attained through the programme of integrated projects in education. Concerning the objective of creating international links it appears that it was realized when the programme was elaborated; however, the programme increases and officializes the exchanges, without that the Federal government intervenes, and leaves to the Quebec government the ability to impose its priorities. The integrated projects do not balance American influence, as it was the intention. The objectif of promotion of French language is partially realized through the publication of articles in French or the Frenchization of the bibliographies ; but the programme results in a perverse effect when French and Quebecer researchers publish jointly in English. The academic cooperation did not favorize teaching improvement of Quebecer professors, as it was an objective; however, it favorized research development. The results were partially attained, because this policy began without any study of the situation.